Odpowiedzi

Najlepsza Odpowiedź!
2009-12-06T20:32:05+01:00
C) y= ⁵/₂x + 1 ,P (-2,3)
a₁=a₂
a₁=⁵/₂
a₂=⁵/₂

y=⁵/₂ x+b
P=(-2,3)
3=⁵/₂ *(-2) +b
3=-5+b
b=3+5
b=8
y=⁵/₂ x +8


d) y= -⁴/₃x +6, P (1/2,-1,6)
a₁=a₂
a₁= -⁴/₃
a₂= -⁴/₃
y= -⁴/₃x +b
P=(½;-1,6)
-1,6= -⁴/₃ * ½ +b
-1 ⁶/₁₀ = -⁴/₆ +b
b=⁴/₆ - 1 ³/₅
b=⁴/₆ - ⁸/₅
b=²⁰/₃₀ - ⁴⁸/₃₀ = -²⁸/₃₀
b = -¹⁴/₁₅

y= -⁴/₃x -¹⁴/₁₅


e) y= √3x - 3, P (2√3,6)
a₁=a₂
a₁= √3
a₂= √3
y= √3x +b
P =(2√3,6)
6=√3*2√3 +b
b=6-2*3
b=6-6
b=0
y= √3x

f)y = -3/2, P(4,4)
a₁=a₂
a₁= 0
a₂= 0
y =4
4 4 4